2017
DOI: 10.1002/eji.201646710
|View full text |Cite
|
Sign up to set email alerts
|

The IL–10/STAT3 axis: Contributions to immune tolerance by thymus and peripherally derived regulatory T‐cells

Abstract: The signal transducer and activator of transcription (STAT) proteins are important mediators for the integration of extrinsic signals provided by cytokines and hormones and thereby adapt cellular processes to their surroundings. In the past decade, the involvement of STAT3 in the regulation of T-cell responses has become a topic of increasing interest. STAT3 is activated in response to multiple cytokines, many of which have been shown to influence T-cell responses. Interestingly, many of these factors have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 96 publications
0
48
0
Order By: Relevance
“…Only the concentration of IL‐17 was higher in Nbeal2 −/− mice than in control mice under the effects of LPS‐induced inflammation, but this difference was not significant. Higher levels of anti‐inflammatory BRMs (IL‐10, IL‐13, and IL‐4) were only observed in Nbeal2 −/− mice after systemic LPS injection ( Table ) , which correlated with their fold increase (Fig. A).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Only the concentration of IL‐17 was higher in Nbeal2 −/− mice than in control mice under the effects of LPS‐induced inflammation, but this difference was not significant. Higher levels of anti‐inflammatory BRMs (IL‐10, IL‐13, and IL‐4) were only observed in Nbeal2 −/− mice after systemic LPS injection ( Table ) , which correlated with their fold increase (Fig. A).…”
Section: Resultsmentioning
confidence: 81%
“…The concentrations of 15 cytokines/chemokines were, therefore, measured with proinflammatory and anti‐inflammatory function, in WT and Nbeal2 −/− mice challenged systematically by LPS. Under the baseline condition (i.e., PBS injection), levels of IL‐10, an anti‐inflammatory BRM, were only higher in WT mice compared with Nbeal2 −/− mice. Systemic LPS injection induced a significant increase in 10 proinflammatory soluble factors in both WT and Nbeal2 −/− mice, including IL‐6, IL‐12, GM‐CSF, IL‐5, IL‐1α, IFN‐γ, TNF‐α, IL‐2, IP‐10, and MIG.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, IL‐35 is required in EBI‐induced STAT3 phosphorylation in DCs. The STAT3/IL‐10 axis also plays roles in other cellular activities, such as contribution to thymus‐derived Treg generation and microbial stimulus‐induced IL‐10 expression . Activation of the STAT3/IL‐10 axis plays a critical role in the anti‐inflammatory process .…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin (IL)‐10, an immunomodulatory cytokine mainly secreted by regulatory T cells, monocytes and macrophages, has important roles in inducing immune tolerance by inhibiting antigen‐specific T‐cell proliferation, downregulating costimulatory molecule and MHC II expression on antigen‐presenting cells, inhibiting DC maturation, and inhibiting the production of proinflammation factors, such as tumour necrosis factor (TNF)‐α, interferon‐γ, IL‐6 and IL‐12 . Some studies reported that IL‐10‐producing DCs mediate tolerogenic effects by inhibiting T‐cell activation and enhancing the differentiation of regulatory T cells, which suggests IL‐10 is a potential therapeutic factor for inducing immunological tolerance after LT. Fas ligand (FasL) expressed on antigen‐presenting cells is a type II transmembrane protein belonging to the tumor necrosis factor superfamily, which combines with Fas expressed on T cells to initiate the apoptosis of specific activated T cells, resulting in the downmodulation of immune responses and maintenance of T‐cell tolerance . DCs overexpressing FasL were previously reported to induce antigen‐specific T‐cell tolerance by promoting T‐cell apoptosis .…”
Section: Introductionmentioning
confidence: 99%